Practicing Possibilities: Parents' Explanations of Unusual Events and Children's Possibility Thinking. Issue 3 (26th May 2016) - Nolan-Reyes, Charlotte; Callanan, Maureen A.; Haigh, Kirsten A.
Abstract : Young children tend to judge improbable events to be impossible, yet there is variability across age and across individuals. Our study examined parent–child conversations about impossible and improbable events and links between parents' explanations about those events and children's possibility judgments in a reasoning task. Regression analyses revealed that parents' speculation about potential mechanisms for improbable events during a parent–child book-sharing activity predicted children's possibility judgments for similar events in an individual task and accounted for more of the variance than children's age. Also, parents' skepticism regarding mechanisms for impossible events was negatively correlated with children's judgments about the possibility of improbable events. Additionally, children's overall causal justifications for their judgments were correlated with parents' talk about speculative mechanisms. Results suggest the importance of conversation with parents for young children's developing understanding of the distinction between impossible and improbable.